Serological Evidence of Bovine Herpesvirus 5 (BoHV-5) in Cattle at the Colombia's Eastern Plains - Pedraza-Ordonez, Francisco; Pablo Lopez, Juan; Alberto Avila, Jaime; Alessi, Antonio Carlos [UNESP]; Flores, Eduardo Furtado (Univ Zulia, Facultad Ciencias Veterinarias, 2011)
Several diseases involve the nervous system of cattle, among which infections with Rabies Virus and Bovine Herpes Virus 5 (BoHV-5) are noteworthy. In order to detect seropositive animals to BoHV-5, 156 Brahman-Zebu bovines blood samples from Colombia's eastern plains were analyzed through seroneutralization assay; the area has a history of animals dying with nervous symptoms and which rule out the disease of rabies. All animals were over one year old and randomly selected from two different herds reporting no vaccination for infectious bovine rhinotracheitis in a period exceeding one year. Results indicated seropositivity for BoHV-5 in 91 cases (58.4%), of which 88 were also seropositive for bovine herpes virus 1 (BoHV-1), while 41 were seronegative for both agents. 22/64 seronegative cases for BoHV-5 were seropositive for BoHV-1 and 2/43 seronegative cases for BoHV-1 were seropositive for BoHV-5, and consequently, these animals could be only infected by encephalitis herpes virus. With these initial findings, emphasis its placed on the need establish the true impact of the disease in Colombia and proposes the epidemiological surveillance of cattle in the region studied in order to establish mechanisms for control of viral infection.
Keywords: Bovine encephalitis; bovine herpesvirus 5; seroneutralization